The treatment of disabled individuals in small, medium‐sized, and large firms. Issue 2 (1st September 2021) - Bacon, Nick; Hoque, Kim
Abstract: Integrating literature on small firm informality and organizational growth and development into Stone and Colella's model of the workplace treatment of disabled individuals, we assess prior claims that disability employment outcomes are better in large firms than in small and medium‐sized firms. Drawing on the principle of equifinality, we propose disability employment outcomes (workforce disability prevalence and disability gaps in contentment and job satisfaction) will not vary by firm size, given both the formalized approach of large firms (disability equality practices, HR specialists, and union recognition), and the more informal approach of small firms (greater job autonomy, a stronger fairness culture, better work‐life balance, and single‐site operations with closer personal relationships) may have benefits for disabled people. Analyzing nationally representative matched employer–employee data, we show that, as anticipated, formalized approaches are more prevalent in large firms (and to an extent medium‐sized firms) and informal approaches are more prevalent in small firms, and disability employment outcomes do not vary by firm size. However, this appears to reflect the ineffectiveness (rather than effectiveness) of characteristics and practices associated with both large firm formality and small firm informality, with both being weakly associated with better disability employment outcomes.